About Pieter Bruegel, The Picture or the infinite sphere. For a theological political reform of understanding: (Palíndromo, 2021)
Bruegel’s paintings stand at the beginning of a period of profound change, of which Spinoza experienced the final episode. The intrinsic unity of a historical period binds the painter and the philosopher together in the common struggle for the freedom of expression. This symmetry of the painter and the philosopher was initially historical. Yet it gave rise to the hypothesis of a different symmetry, this time epistemological, between image and concept. This double symmetry lies at the beginning of my research questions. As with Spinoza a century later, did Bruegel’s pictorial work already produce a particular theoretical device which, in its domain, reflected on – and from – the distinction between imagination and intellect? This question, together with the conviction of a cognitive activity of art, supported at the same time my working hypothesis and my epistemological motivations.
Keywords: Effectual truth; Imagination; Immanence; Second nature; Infinite sphere